ENHANCING ENGLISH LANGUAGE TEACHING THROUGH ARTIFICIAL INTELLIGENCE AND DIGITAL TECHNOLOGIES: THE PEDAGOGICAL POTENTIAL OF CHATGPT, QUIZLET, AND KAHOOT - Salomova Zamira Samadovna (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study examines the integration of artificial intelligence and digital technologies into English language teaching to enhance students’ communicative competence. The author analyzes the pedagogical functions of AI-based tools such as OpenAI ChatGPT, Quizlet, and Kahoot and proposes a practical model for their classroom application. Experimental results show significant improvements in vocabulary, grammar, speaking skills, and learner motivation. The findings confirm the effectiveness of digital technologies in creating a more interactive and student-centered learning environment.